Political campaign communication principles and practices - Denton, Robert E. Jr. 1953-; Trent, Judith S.; Friedenberg, Robert V. 1943- (Rowman & Littlefield, 2019)
Political Campaign Communication, Ninth Edition uses a speech-communication perspective to examine how elective politics contributes to our knowledge and understanding of the electoral process. This book explains how principles and practices central to election campaigns affect America's electoral history
Keywords: Political campaigns; Communication in politics; Electronic books